2017
DOI: 10.1016/j.jemermed.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Services Perspectives on Identifying and Reporting Victims of Elder Abuse, Neglect, and Self-Neglect

Abstract: Background Emergency Medical Services (EMS) providers, who perform initial assessments of ill and injured patients, often in a patient’s home, are uniquely positioned to identify potential victims of elder abuse, neglect, or self-neglect. Despite this, few organized programs exist to ensure EMS concerns are communicated to or further investigated by other health care providers, social workers, or the authorities. Objective To explore attitudes and self-reported practices of EMS providers surrounding identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 44 publications
0
40
0
5
Order By: Relevance
“…This too, was not unique to Davis—we observed this in other study participants who reported mistreatment. Our findings, therefore, may contribute to the literature on elder abuse where scholarship has largely been concerned with its prevention (Pillemer, Burnes, Riffin, & Lachs, 2016) and identification (Lachs & Pillemer, 2015; Rosen et al, 2017), rather than the mitigation of its sequelae. Specifically, our findings point to the lack of appropriate services available to older residents of high-crime neighborhoods after they report the abuse to the authorities, a concerning topic that calls for further investigation.…”
Section: Limitation Of Health Care and Social Servicesmentioning
confidence: 68%
“…This too, was not unique to Davis—we observed this in other study participants who reported mistreatment. Our findings, therefore, may contribute to the literature on elder abuse where scholarship has largely been concerned with its prevention (Pillemer, Burnes, Riffin, & Lachs, 2016) and identification (Lachs & Pillemer, 2015; Rosen et al, 2017), rather than the mitigation of its sequelae. Specifically, our findings point to the lack of appropriate services available to older residents of high-crime neighborhoods after they report the abuse to the authorities, a concerning topic that calls for further investigation.…”
Section: Limitation Of Health Care and Social Servicesmentioning
confidence: 68%
“…25 Diversos estudos indiciam tratar-se, efetivamente, de um problema comum. Ainda assim, muitos dos profissionais de saúde que trabalham com pessoas idosas afirmam nunca terem detetado um caso de abuso de idosos, 15,17 situação que suporta a tese defendida por alguns autores de que os casos reportados constituem somente a «ponta do icebergue» 6,15,24 e que mais de 80% dos casos de abuso de idosos nunca são denunciados ou reportados a nenhuma entidade, 6,18,26 apesar de se tratar de uma situação transversal a todas as classes socioeconómicas a nível mundial. Na mesma linha, a literatura revela que somente um em cada 24, [25][26][27] um em cada 14 28 ou um em cada cinco casos de abuso de idosos 29 são efetivamente denunciados.…”
unclassified
“…A relevância médica do abuso é amplamente reconhecida atendendo às consequências nefastas que acarreta para a saúde da vítima, quer em termos de aumento da mortalidade 2,9,16,[26][27]30,33,36 quer de morbilidade, com subsequente diminuição da qualidade de vida 1,5,9,11,21,36 em comparação com idosos que não sofreram abuso. Adicionalmente, tem sido associado a um aumento do risco de recorrência ao serviço de urgência, [30][31]33 hospitalização [26][27][30][31]33 e institucionalização em lar, 26,[30][31]33 bem como a depressão 8,[26][27]30,32 e ansiedade. 16,27,32 Alguns autores referem ainda o desenvolvimento de isolamento social por parte da vítima, 8,32 assim como sentimentos de culpa 8 e stress pós-traumático.…”
unclassified
“…[34][35][36] Several studies have evaluated EMS providers' attitudes toward elder abuse and established that, although prehospital providers believe that elder abuse is prevalent and important, a lack of EMS protocols and training specific to elder abuse limit their potential to identify this problem and take appropriate action. [37][38][39] EMS protocols, which state or regional EMS medical directors establish, define the operating procedures that EMS providers to follow. Although EMS providers can provide care outside of the protocols and have the ability to contact a medical director for guidance or oversight, for the most part, protocols and the training that accompanies these protocols constrain EMS care.…”
mentioning
confidence: 99%
“…Thus, EMS providers report that lack of protocols creates a challenge for them in identifying and reporting cases of elder abuse. 39 Recognizing the important role of protocols in EMS care, we sought to describe current practices regarding elder abuse by reviewing publicly available statewide EMS protocols. Because there are important similarities between elder and child abuse that make their comparison compelling and relevant, protocols were also reviewed for child abuse to compare the presence and level of detail of elder abuse and child abuse protocols.…”
mentioning
confidence: 99%